Effects of binder addition on the surface generation mechanism of WC/Co during high spindle speed grinding (HSSG). (September 2016) - Zhang, Quanli; To, Suet; Zhao, Qingliang; Guo, Bing; Wu, Mingtao
Abstract: High spindle speed grinding (HSSG) of WC/Co and binderless WC was conducted to study the effects of binder addition on surface generation mechanism. To help to explain the role of Co binder, Vickers-indentation and nano-indentation test were also conducted on the polished WC/Co and binderless WC workpiece. The indentation results showed that even though the addition of Co binder could obviously improve the toughness of bulk materials, non-uniform surface plastic deformation can be induced by the varied hardness of composing phases in nanoscale, indicated by the shape of load-displacement curves at low loads. Moreover, except for the scratching grooves and feed marks, the machined WC/Co surface was covered by randomly distributed micro-pits resulted from the dislodgement of hard particles in comparison with the binderless WC. Fast Fourier Transform (FFT) analysis confirmed the obvious contribution of binder addition to the spatial frequency at 148.1 1/mm than the feed component. Moreover, the results showed that the machined surface experienced no evident oxidation with minimum quantity lubrication, but a deformed surface layer formed under the dynamic pressure of the diamond grits during grinding. Highlights: Co binder addition deteriorates the surface finish of WC/Co, even though improving the toughness of bulk materials; Micro-pits formed with the dislodgement of WC particles, and non-uniform material removal rate between composing phases; Fast Fourier Transform (FFT) analysis confirmed the obvious contribution of Co binder addition; A deformed layer of about 2 μm was induced during grinding.